Islamic Storytelling Training to Improve Teachers' Pedagogical Competence in Instilling Moral Values in Elementary School Students - Herni Hartati (Jurnal Masyarakat Mengabdi, 2026)
Islamic storytelling training is a strategy to improve teachers' pedagogical competence in instilling moral values in elementary school students. This community service activity aimed to enhance teachers' understanding and skills in Islamic storytelling methods and create program sustainability through the Participatory Action Research (PAR) approach. The activity was conducted at SD Negeri 020 Jaya Mukti, Dumai, in June 2025, targeting 30 teachers. The training methods included interactive lectures, demonstrations, simulations, group discussions, and direct mentoring. Evaluation instruments included pre-test and post-test (20 multiple-choice questions), observation sheets (five skill aspects scored 1-4), participant satisfaction questionnaires (Likert scale 1-5), and Focus Group Discussions (FGD). The results showed a significant improvement in teachers' understanding from a pre-test mean score of 58.4 to 86.2 on the post-test (47.6% increase; p<0.001). Teachers' storytelling skills improved from an average of 11.3 to 15.7 (skilled category), with 80% of teachers achieving the skilled category, exceeding the 75% target. The aspect of extracting moral values showed the highest improvement (88.9%). Participant satisfaction was very high (mean 4.6 out of 5.0) with 93.3% of teachers satisfied. Program sustainability was achieved through the establishment of the Islamic Storytelling Teacher Community (KUGARBI), the issuance of a Principal's Decree on regular storytelling every Friday morning, and classroom implementation by 90% of teachers. The PAR-based Islamic storytelling training proved effective in improving teachers' pedagogical competence and is recommended for replication in other schools.